Building A Community: Strategies For Scalable Growth In The Digital Health Hub - Navarro Ramirez, Sofia (Digital Repository of Theses, 2025)
This thesis examines the developments and implementation of community growth strategies withing the Digital Health Hub, an online platform designed to enhance public understanding and promote the responsible use of digital health tools, The research centers on creating a collaborative and inclusive digital environment where expert, volunteers and everyday users work together to bridge the gap between rapidly evolving digital health technologies and public awareness. As the digital health world expands, the demand for informed usage of tools such as telemedicine platforms, health apps, wearable devices, and AI-driven health or non-health information sources becomes increasingly urgent. The thesis outlines a strategic framework that utilizes social media outreach, people, experts, and volunteers’ engagement, and structured communication efforts to improve community participation. It highlights the importance of building trust, improving accessibility, and influencing health. Related decision-making. A key objective of this study is to establish a model in which health professionals and citizens collaboratively contribute to digital health literacy. The finding emphasizes the community-driven initiatives in promoting digital health discussion, inclusion, supporting better individual or public decisions, and enabling AI experts, policymakers, companies, the pharmaceutical industry, etc., to develop together a more reliable and user-friendly digital environment for everyone.